Diversity and interactions among triatomine bugs, their blood feeding sources, gut microbiota and Trypanosoma cruzi in the Sierra Nevada de Santa Marta in Colombia. (2023)
Chagas disease remains a major neglected disease in Colombia. We aimed to characterize Trypanosoma cruzi transmission networks in the Sierra Nevada de Santa Marta (SNSM) region, to shed light on disease ecology and help optimize control strategies. Triatomines were collected in rural communities and analyzed for blood feeding sources, parasite diversity and gut microbiota composition through a metagenomic and deep sequencing approach. Triatoma dimidiata predominated, followed by Rhodnius prolixus, Triatoma maculata, Rhodnius pallescens, Panstrongylus geniculatus and Eratyrus cuspidatus. Twenty-two species were identified as blood sources, resulting in an integrated transmission network with extensive connectivity among sylvatic and domestic host species. Only TcI parasites were detected, predominantly from TcIb but TcIa was also reported. The close relatedness of T. cruzi strains further supported the lack of separate transmission cycles according to habitats or triatomine species. Triatomine microbiota varied according to species, developmental stage and T. cruzi infection. Bacterial families correlated with the presence/absence of T. cruzi were identified. In conclusion, we identified a domestic transmission cycle encompassing multiple vector species and tightly connected with sylvatic hosts in the SNSM region, rather than an isolated domestic transmission cycle. Therefore, integrated interventions targeting all vector species and their contact with humans should be considered.